MODEL PERILAKU ANGGOTA KLUB MOTOR DI BENGKAYANG: PENDEKATAN EKSPLORATORIS - Pramatatya Resindra Widya; Aloysius Hari Kristianto; Jimmi Jimmi (Politeknik Negeri Ambon, 2020)
The aim of this study is to explore the antecedents and consequences of people’s intention to join the brand community. Nowdays, brand community has become a new marketing channel for marketers to enter the market. This exploratory research conducted with Qualitative methods with ethnography approach and some motorbike clubs as the participant. This research found a new concept of behavioral models in brand community and it can be use for behavioral sciences studies especially in consumer behavior.